EXPLORING THE SYNERGY OF GREEN INNOVATION AND DIGITAL TRANSFORMATION FOR ENHANCING SME PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Mentari, Sriyani; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
Green innovation and digital transformation are one of the crucial components in dealing with industrial development and environmental issues for SMEs. Each has an important and interrelated role in helping the performance of SMEs. This study aims to identify how the collaboration of green innovation and digital transformation in improving the performance of SMEs with a systematic literature review technique. This research uses a systematic search strategy to collect journal articles from the Scopus and Web of Science databases for the last 5 years. The results of the systematic review revealed that green innovation and digital transformation collaborate in improving the quality of information and resources that lead to effective SME operational processes with efficient costs so to create market competitiveness and improve SME performance both financial and non-financial. The results of this study can be taken into consideration for SMEs to implement green innovation and digital transformation in their operations.